SIFAT REOLOGI DAN STABILITAS FISIK MINUMAN EMULSI MINYAK SAWIT - Nurlita Dianingsih; Eko Hari Purnomo; Tien R. Muchtadi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
Palm oil emulsion drink is one of the food diversification product, containing high provitamin-A. The dispersed phase of the emulsion is palm olein, while the rest was water as the dispersion medium (ratio 7:3). The low content of dispersion medium in the emulsion caused the rheological properties, droplet size and distribution, as well as its level of stability to be different from other commercial product of beverage emulsion. This research investigated the effect of storage time on the rheological properties, droplet size distributions and stability of the emulsion. The emulsion morphology was observed by polarized light microscopy, while its size and distribution were analyzed by dynamic light scattering technique using Zetasizer. The rheological analysis, including the determination of the flow behavior and consistency index, were measured using a rotational dial reading viscometer. The results showed that increasing of storage time led to increased droplet size and distribution (d4.3 value from 4.83 to 6.12 µm, value of flow behavior index from 0.9782 to 0.9873, and consistency index from 3.473 to5.047 Pa.sn). However, this condition also caused a decrease in emulsion stability (from 0.880 to 0.823). According to Pearson’s correlation coefficients, the droplet size was negatively correlated with emulsion stability (R = -0.907; α = 0.01). However, the droplet size were positively correlated with the flow behavior index (R = 0.778; α = 0.01) and consistency index (R = 0.939; α = 0.01). These results may help formulate palm oil emulsion drink with improved stability and shelf-life.